THE ROLE OF PERCEIVED RELEVANCE IN MEDIATING THE EFFECT OF AD PERSONALIZATION AND CONTENT SUITABILITY ON REPURCHASE INTENTION OF GLAD2GLOW PRODUCTS IN TIKTOKSHOP. - Abdul Fahri Sakti Ali Tuasikal; Zakiyah Zahara; Ponirin; Mohammad Zeylo Auriza (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to examine the extent to which ad personalization and content suitability influence repurchase intention, with perceived relevance acting as a mediating variable in consumers of Glad2Glow products on TikTok Shop. The research approach used a quantitative method with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis of 100 respondents who actively use TikTok and have interacted with Glad2Glow products. The results showed that both ad personalization and content suitability have a positive and significant influence on perceived relevance and repurchase intention. In addition, perceived relevance was proven to act as a mediator that strengthens the relationship between the two variables on repurchase intention. These findings indicate that digital marketing communication efforts that focus on message suitability and relevant experiences can improve consumer perceptions, strengthen emotional connections with brands, and foster loyalty to Glad2Glow products on the TikTok Shop platform.